An unusual new genus and a new species of Buccinulidae (Neogastropoda) from the Magellanic Province - Kantor, Yu . (2009)
A new genus and species of the family Buccinulidae is describedfrom the Southwestern Atlantic in Argentine waters.Jerrybuccinum malvinense new genus and species combinesthe conchological characters of Fasciolariidae with the radulaof Buccinulidae.